2015
DOI: 10.12740/pp/32566
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in severe mental disorders.

Abstract: The prevalence of obstructive sleep apnoea (OSA) is estimated to be 3-7.5% in men and 2-3% in women. In mentally ill population it is even higher, as these patients are a high risk OSA group. The aim of the paper was a review of literature about the prevalence of sleep apnoea in patients with schizophrenia, bipolar disorder and recurrent depressive disorder.The available data show that OSA is present in 15-48% of patients with schizophrenia, 21-43% of patients with bipolar disorder and 11-18% of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
1
23
1
2
Order By: Relevance
“…Based on the results, the risk for OSA in patients with cTRD is much greater than the general population of Kermanshah. The main finding is consistent with studies reporting an increased incidence of OSA symptoms in patients with depression, building a long-standing co-occurrence of mood and sleep disorders (11,24). The results are also consistent with studies indicating that untreated OSA patients might show higher depressive symptoms (38)(39)(40).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results, the risk for OSA in patients with cTRD is much greater than the general population of Kermanshah. The main finding is consistent with studies reporting an increased incidence of OSA symptoms in patients with depression, building a long-standing co-occurrence of mood and sleep disorders (11,24). The results are also consistent with studies indicating that untreated OSA patients might show higher depressive symptoms (38)(39)(40).…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned, several studies have already investigated the association between MDD and coexisting OSA (18,(24)(25)(26)(27). However, a few studies have examined if coexisting OSA could lead to treatment-resistance in MDD or a bidirectional association could be anticipated (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Szaulińska et al10 reported that obstructive sleep apnea (OSA) is present in 11%–18% of patients with MDDs, 15%–48% of patients with schizophrenia, and 21%–43% of patients with bipolar disorder, but in only 5% of the general population 11. One study has shown that patients diagnosed with OSA are at an increased risk of a diagnosis of depression 12.…”
Section: Introductionmentioning
confidence: 99%
“…One study has shown that patients diagnosed with OSA are at an increased risk of a diagnosis of depression 12. Additionally, the symptoms of sleep apnea might imitate the symptoms of depression, including sleep disturbance, general fatigue, decreased volition and judgment ability, aggravated cognitive impairment, and a lower quality of life 10. In addition, OSA might exacerbate symptom severity in MDDs 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation